1994
DOI: 10.1021/bi00198a014
|View full text |Cite
|
Sign up to set email alerts
|

Adipsin/Acylation Stimulating Protein System in Human Adipocytes: Regulation of Triacylglycerol Synthesis

Abstract: Through their capacity to store fatty acids as triacylglycerol molecules, adipocytes serve a vital physiologic role. This study presents further evidence that this process can be modulated in human adipocytes by the adipsin/acylation stimulating protein (ASP) pathway and suggests a novel function for the product of this system--ASP. The data demonstrate the following: (1) ASP stimulates triacylglycerol synthesis within adipocytes, and this occurs to a greater extent in differentiating than undifferentiated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0
6

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 31 publications
5
111
0
6
Order By: Relevance
“…Complement protein C3 was measured because it is a cytokine-inducible acute-phase plasma protein [20] and vital to all three complement activation pathways and defence against invading micro-organisms [21]. It is synthesized also in the adipose tissue [22] and has a connection to lipid metabolism through its cleavage product acylation stimulating protein (ASP) [23]. It has a critical role in triacylglycerol (TG) synthesis within adipocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Complement protein C3 was measured because it is a cytokine-inducible acute-phase plasma protein [20] and vital to all three complement activation pathways and defence against invading micro-organisms [21]. It is synthesized also in the adipose tissue [22] and has a connection to lipid metabolism through its cleavage product acylation stimulating protein (ASP) [23]. It has a critical role in triacylglycerol (TG) synthesis within adipocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, analyses were performed before and after interventions. The patients had been requested to consume a cholesterol-lowering diet (less than 30% of daily energy as fat and daily cholesterol intake < 200 mg, (19)) and were treated with gemfibrozil (Gevilon®, G decke Inc.) 900 mg at bedtime. They were advised to adhere to this diet during the experimental period (6 months).…”
Section: Patientsmentioning
confidence: 99%
“…A certain C4 allotype (C4B*QO) had higher prevalence in men with myocardial infarction (18). C3 was reported to be involved in the regulation of the adipsin/acylation stimulating protein system which seems to play a pivotal role in regulation of triacylglycerol removal from plasma (19). It was found that acylation stimulating protein is identical with the cleavage product of complement factor C3, named C3a-desArg, and stimulates triacylglycerol synthesis in human adipocytes.…”
mentioning
confidence: 99%
“…8,9 ASP is a potent stimulator of free fatty acid esterification into storage triglyceride in human adipocytes in vitro. 5,6,10 Recent studies indicate that chylomicrons and insulin increase both ASP and C3 production in human adipocytes. [11][12][13] While no direct role for C3 has been proposed, ASP appears to be an important determinant of postprandial lipemia in both human 14 and mouse models.…”
Section: Introductionmentioning
confidence: 99%